Training on Climate Risk Management in Agricultural Advisory Services in Senegal - Sine, Bassirou; Faye, Babacar; Thiaw, Cheikh; Sy Diallo, Babacar (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The phenomenon of climate change encompasses all sectors of life, and its impact on the agricultural sector (farming and livestock breeding) is well established. Faced with these challenges of adaptation and survival, it is important to raise awareness among all those involved (technicians and producers) of the basic concepts and decision-support tools needed to derive maximum benefit from agricultural activities. It was against this backdrop that AICCRA set up a train-the-trainer program with the support of universities, agricultural technicians, producers' organizations and agricultural technology extension services. A model curriculum was selected at an earlier event in Dakar from December 05 to 10, 2022 (Fleur de Lys Point E). A train-the-trainer workshop was organized in Saly from March 06 to 16, 2023 to validate and improve the training modules. The AICCRA project (Accelerating Impacts of CGIAR Climate Research in Africa), is a three (3) year project (2021-2023) funded by the World Bank (IDA) in six (6) African countries: Ethiopia, Kenya, Zambia, Ghana, Mali and Senegal. The main objective of AICCRA-Senegal is to strengthen the technical, institutional and human capacities needed to improve the transfer of climate-related information, decision-making tools. and technologies in support of scaling-up efforts to strengthen the resilience of agricultural and livestock value chains, particularly in arid zones. As part of this training program, AICCRA aims to improve and facilitate access to climate information services and climate-smart agricultural technologies for the project's target farmers, via extension agents. AICCRA therefore aims to help build producers' resilience and make it easier for them to understand weather and climate phenomena, so they can forecast and plan their farming activities effectively. Capacity building for intermediate users, in particular of agricultural extension and advisory services (EAS) in Senegal and five other target countries is a key element of AICCRA's strategy for achieving this objective.